THE IMPACT OF PRICE, SERVICES, QUALITY OF SERVICES AND PRODUCTS TOWARD PURCHASING DECISION OF CUSTOMERS IN PT. NUSIRA MEDAN - Silalahi, Esther Lina; Butarbutar, Meysin; Sihombing, Zetty; Ginting, Nurmaidah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The objective research was a company of PT. Nusira Medan. This study which aimed in determining the impact of prices which were influenced by using exchange rate could be stabilized or unstabilized due to inconsistent of prices over time, by reviewing the quality of provided services. It was acceptable by the customers were not complain about receiving in services existing. Furthermore, the products of quality provided of the company that could satisfy the customers in order to make purchases for the next time, by paying more attention of the price given, especially in improving the service and product quality to improve decisions purchasing at PT. Nusira Medan. Furthermore, the theory which contained of this study was a theory that related of price, services quality and product quality. The approaching of this research used the quantitative approaching and the research type was descriptive quantitative. The methods of data collections which made in interviewing, questionnaire and documentation studying. The population were the customers whom made purchases at PT. Nusira Medan that consisted of 100 customers. The results of the determinating test, were Adjusted R Square of 0.526, could show 52.6% in purchasing of variable decisions could be clarified of price variables and quality of services and product. This study can be concluded partially which price variables and service quality took the positive and significantly effect, thus the product variable of quality gained the positively and insignificant effect. Simultaneously, it also took the positively and significantly influence based on the purchasing of customer decision in PT. Nusira Medan. Keywords: Price, services of quality, product quality, purchasing of customer decision